Principles and practice of clinical parasitology [ - Gillespie, S. H.; Pearson, Richard D. (Principles and Practice Series, 2001)
A comprehensive account of protozoan and metozoan diseases in modern clinical practice, with orientation towards clinical management of parasitic infections. In the past, parasitology was considered as an obscure subject of little relevance to the majority of clinicians and microbiologists. Over the last decade, however, much has happened to change this, not least the explosion in foreign travel